The Effect of Multipath on Single Frequency C/A Code Based GPS Positioning - Dammalage, T. L. (Engineering, Technology & Applied Science Research, 2018)
The differential GPS (DGPS) technique is one of the most popular and comparatively accurate techniques available to enhance the positioning accuracy by minimizing most of the common errors. However, the ultimate accuracy of the user location depends on the remaining non-common errors (multipath, receiver clock, and noise), which occur at the points of observation and reference. Out of these errors, multipath is the most dominant and challenging error to predict and minimize. Single frequency C/A code based GPS receivers are popular due to their comparatively low cost compared to dual frequency (L1/L2) GPS receivers. This paper focuses on evaluating the effect of multipath error on single frequency C/A code based GPS positioning. For the analysis, 72,000 continuous GPS observations with one-second interval under four different multipath environments were conducted by utilizing three geodetic GPS units. Accordingly, the observations with more than 5cm on the 2D positional error, created by the effected multipath, were always less than 25%. Here, an average of 16% of observations exceeded 20cm in 2D positional error. Further, it was noted that the presence of multipath introduces significantly higher and comparatively lower 3D positional errors on DGPS observations. This could be due to the compensation of negative and positive effects caused by the multipath and other remaining non-common mode errors at the reference and user stations. In addition, C/A code based single frequency GPS observations were significantly influenced by multipath, not only by the close-by reflectors but also by the ground surface. The effect of multipath was about 50% of the total 3D positional error for the four tested multipath environments.